2017
DOI: 10.1111/asj.12874
|View full text |Cite
|
Sign up to set email alerts
|

Dietary rice improves growth performance, mucosal enzyme activities and plasma urea nitrogen in weaning piglets

Abstract: In this study, we evaluated the nutritional functions of rice for weaning piglets. Sixteen weaning piglets with an average initial weight of 7.2 kg were divided into two groups. One group was fed a corn-soybean meal based diet, and the other was fed a rice-soybean meal based diet, containing 50% corn and rice, respectively. A 2 weeks growth trial was conducted and growth performance, intestinal mucosal enzyme activities and plasma urea nitrogen were measured. The average daily gain in rice-fed piglets was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 22 publications
1
13
1
Order By: Relevance
“…The clear difference in FE and ADFI between our previous report and this report could partially be explained by the difference in total lysine content in the diets. Lysine content in the diets of this experiment was 15.5-16.3 g/kg, which satisfy the NRC feeding standard (NRC, 2012); however, in our previous report (Yagami & Takada, 2017), lysine content was 12.9-13.0 g/kg, which satisfied the Japanese feeding standard. Expected weight gain in Japanese feeding standard is 250 g/day, which is lower than the ADG (468 g/day) observed in our previous report.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…The clear difference in FE and ADFI between our previous report and this report could partially be explained by the difference in total lysine content in the diets. Lysine content in the diets of this experiment was 15.5-16.3 g/kg, which satisfy the NRC feeding standard (NRC, 2012); however, in our previous report (Yagami & Takada, 2017), lysine content was 12.9-13.0 g/kg, which satisfied the Japanese feeding standard. Expected weight gain in Japanese feeding standard is 250 g/day, which is lower than the ADG (468 g/day) observed in our previous report.…”
Section: Discussioncontrasting
confidence: 55%
“…This report is, to our knowledge, for the first to show higher FE in rice-fed piglets than in corn-fed piglets. In our previous report (Yagami & Takada, 2017), the FE between corn-and rice-fed piglets was not different, although ADG and ADFI were significantly higher in rice-fed piglets than in corn-fed piglets. The clear difference in FE and ADFI between our previous report and this report could partially be explained by the difference in total lysine content in the diets.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…It is generally utilized for human food, but it is also used as an animal feed. In studies on piglets and broilers, some researchers have recently suggested that feeding piglets and broilers a rice diet instead of a corn diet improves growth performance (Ebling et al., 2015; Fujimoto, Fujita, & Takada, 2018; González‐Alvarado, Jiménez‐Moreno, Lázaro, & Mateos, 2007; Mateos, Martin, Latorre, Vicente, & Lazaro, 2006; Tasaka, Tachihara, Kagawa, & Takada, 2020; Vicente, Valencia, Pérez‐Serrano, Lázaro, & Mateos, 2008; Yagami & Takada, 2017). Feeding rice to pigs and chickens is a common practice all over the world, and interest in the use of rice‐based diets in broiler production has recently increased in Japan.…”
Section: Introductionmentioning
confidence: 99%